Surgical anatomy of the supraglottic larynx using the da Vinci robot. Issue 8 (27th November 2013) - Goyal, Neerav; Yoo, Frederick; Setabutr, Dhave; Goldenberg, David
Abstract Background Transoral robotic surgery (TORS) has facilitated organ‐preserving surgery of the larynx. It has also presented a change in the surgical perspective. We performed cadaveric dissections using the robot to highlight the vascular and muscular anatomy of the supraglottic larynx. Methods Cadaveric specimens underwent injection of their vasculature, and after injection a robotic surgical system was used to perform a transoral dissection of the supraglottic region. Care was taken to preserve anatomic landmarks and microvascular structures. Results Five fresh frozen cadaveric human heads were injected with silicone and used for the dissection. The superior laryngeal neurovascular bundle was identified and an absent superior laryngeal vein (SLV) was noted on 1 specimen. Using the robotic endoscope allowed us to visualize and identify the microvasculature of the head and neck. Conclusion These dissections revealed anatomic variations in the superior laryngeal neurovascular bundle and also highlighted the differences in view using a surgical robotic system. © 2013 Wiley Periodicals, Inc. Head Neck 36: 1126–1131, 2014